2006
DOI: 10.1038/sj.emboj.7601152
|View full text |Cite
|
Sign up to set email alerts
|

Myc influences global chromatin structure

Abstract: The family of myc proto-oncogenes encodes transcription factors (c-, N-, and L-Myc) that regulate cell growth and proliferation and are involved in the etiology of diverse cancers. Myc proteins are thought to function by binding and regulating specific target genes. Here we report that Myc proteins are required for the widespread maintenance of active chromatin. Disruption of N-myc in neuronal progenitors and other cell types leads to nuclear condensation accompanied by large-scale changes in histone modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
304
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(333 citation statements)
references
References 64 publications
24
304
3
2
Order By: Relevance
“…Consistent with the hypothesis that EZH2 activity controls global H3 methylation, we found that total cellular H3K27me3 levels were dramatically elevated by both MYC and EZH2/S21A expression (Kaur and Cole 2013). Previous studies showed that MYC can increase total cellular levels of the activating histone modifications, acetylated H3 and acetylated H4 (Knoepfler et al 2006), but this experiment showed a simultaneous increase in the repressive H3K27me3 modification. Because the EZH2/S21A mutant can completely recapitulate the effect of MYC on H3K27me3 levels, this is compelling evidence that MYC acts through reduced phosphorylation of EZH2.…”
Section: Ezh2 Activation Is Sufficient To Account For Myc-mediated Resupporting
confidence: 75%
“…Consistent with the hypothesis that EZH2 activity controls global H3 methylation, we found that total cellular H3K27me3 levels were dramatically elevated by both MYC and EZH2/S21A expression (Kaur and Cole 2013). Previous studies showed that MYC can increase total cellular levels of the activating histone modifications, acetylated H3 and acetylated H4 (Knoepfler et al 2006), but this experiment showed a simultaneous increase in the repressive H3K27me3 modification. Because the EZH2/S21A mutant can completely recapitulate the effect of MYC on H3K27me3 levels, this is compelling evidence that MYC acts through reduced phosphorylation of EZH2.…”
Section: Ezh2 Activation Is Sufficient To Account For Myc-mediated Resupporting
confidence: 75%
“…Intriguingly, we found that the percentage of H3 in this fraction is increased in both the Em-MYC pre-B and the lymphoma cells relative to wild-type cells. This suggests that a profound global change in chromatin solubility occurs upon overexpression of MYC, which is consistent with the global condensation that occurs with loss of N-MYC from neural progenitor cells (Knoepfler et al 2006). In addition, because the amount of soluble chromatin recovered from lymphoma cells increased relative to that from Em-MYC pre-B cells, increases in chromatin solubility are not simply consequences of MYC-driven cellular proliferation.…”
Section: Chromatin Solubility Increases During Myc-induced Oncogenesissupporting
confidence: 57%
“…They regulate transcription by recruiting histone acetyltransferases (HAT) (McMahon et al 2000) and other chromatin-modifying factors (Eilers and Eisenman 2008). Changes in MYC levels have been shown to have widespread effects on chromatin marks (Knoepfler et al 2006). Importantly, MYC has also been shown to induce EZH2 expression in other cancers (Koh et al 2011;Salvatori et al 2011).…”
Section: Myc Proteins and The Epigenetic Landscape In Medulloblastomamentioning
confidence: 99%